2011
DOI: 10.1021/jp208734f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Study of Bonding and Optical Properties of Self-Assembly Metallophthalocyanines Complexes on a Gold Surface. A Survey of the Substrate–Surface Interaction.

Abstract: The formation of self-assembly monolayers (SAMs) based on a gold substrate and a thiolate ligand as "anchor" fragment of metallophtalocyanine has been employed as strategy toward the obtention of modified electrodes. In this Article, the formation of SAM's involving iron and cobalt phtalocyanines anchored by 4-aminothiophenol (4-ATP) and 4-mercatopyridine (4-MP) to the Au(111) surface is explored by both experimental and theoretical studies for a better understanding of their bonding pattern and optical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 70 publications
2
30
0
Order By: Relevance
“…A number of possible explanations have been suggested for this effect. Both theoretical and experimental work [26,109,122] indicate that the while the axial ligand increases the physical distance between the gold surface and various metal phthalocyanines, it donates charge towards both, thereby improving the electronic interaction between the two. This changes the nature of the interaction between the metal center and oxygen dimers, reducing the activation energy for the single electron transfer rate determining step for the ORR.…”
Section: Cobalt Macrocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of possible explanations have been suggested for this effect. Both theoretical and experimental work [26,109,122] indicate that the while the axial ligand increases the physical distance between the gold surface and various metal phthalocyanines, it donates charge towards both, thereby improving the electronic interaction between the two. This changes the nature of the interaction between the metal center and oxygen dimers, reducing the activation energy for the single electron transfer rate determining step for the ORR.…”
Section: Cobalt Macrocyclesmentioning
confidence: 99%
“…Image used from Ly et al [117]. Published by The Royal Society of Chemistry surface of these nanomaterials [109,122]. These modified carbon nanotubes have also been used to bind CoPc previously [96].…”
Section: Cobalt Macrocyclesmentioning
confidence: 99%
“…This effect has also been observed using other types of supports, such as gold, where the FeN4 complexes are coordinated to a selfassembled monolayer (SAM). [55][56][57][58][59] Heat treatment modifies the ligation around the Fe center shifting the Fe(III)/(II) to more positive values. [60] The combined effect of an optimized FePc redox potential and optimized bonding or adsorption of various FePc's on a carbon allotrope surface has not yet been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…2, mainly due to an articial interaction with the cluster border that causes a shortening in the distance between the molecule and the surface's plane that is appreciated in the systems without the dispersion correction. The incorporation of model1, the smaller cluster in this study, was motivated by previous studies, [34][35][36] which have shown the usefulness of this cluster size in SAM's based electrocatalysis and that will allow to evidence the edge effects for this cluster size. Further results will be presented in the ESI.…”
Section: Resultsmentioning
confidence: 99%